2013
DOI: 10.1108/gm-01-2013-0011
|View full text |Cite
|
Sign up to set email alerts
|

Career persistence of women software professionals in India

Abstract: Purpose -This paper seeks to explore career centrality, belief in gender disadvantage, and career success definition as the determinants of career persistence among women software professionals in emerging economies like India. The control variables used are marital and parental status. Design/methodology/approach -A survey questionnaire was administered to 190 software women professionals and statistical analyses were used to test the hypotheses. Findings -Belief in gender disadvantage and objective success d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(78 citation statements)
references
References 51 publications
1
77
0
Order By: Relevance
“…Consistent with previous research, outcome expectations were found to be directly predictive of engineering students' intentions to pursue a high-tech career. The significant relationship from outcome expectations to interest and to intentions to pursue a high-tech career may also reflect students' attitudes toward high-tech occupations, which are seen as high paying and prestigious compared to other fields (Srinivasan et al, 2013). Occupational self-efficacy, however, was not found to be directly predictive;…”
Section: Integration Of Interest Model Choice Model and Support Andmentioning
confidence: 88%
See 3 more Smart Citations
“…Consistent with previous research, outcome expectations were found to be directly predictive of engineering students' intentions to pursue a high-tech career. The significant relationship from outcome expectations to interest and to intentions to pursue a high-tech career may also reflect students' attitudes toward high-tech occupations, which are seen as high paying and prestigious compared to other fields (Srinivasan et al, 2013). Occupational self-efficacy, however, was not found to be directly predictive;…”
Section: Integration Of Interest Model Choice Model and Support Andmentioning
confidence: 88%
“…In accordance with Frenette's definition, the high-tech domain can be said to include disciplines such as computer science, computer engineering, electrical and electronics engineering, software engineering, systems engineering, information communication technology, and information systems. High-tech jobs are considered to be one of the fastest growing, well-paid occupations (Betz, 2005;Ferguson, Hitt, & Tambe, 2013) associated with high prestige (Srinivasan, Murty, & Nakra, 2013), and also an important source of economic growth (Wright & Dwyer, 2003).…”
Section: High-tech: a Gendered Occupationmentioning
confidence: 99%
See 2 more Smart Citations
“…Most theory has relied on empirical data from Europe and North America, with a consequential European and North American focus. The recent research highlights socio‐cultural, religious and institutional challenges facing working women in south Asia (Haq ; Saifuddin, Dyke and Rasouli ; Pio and Syed ; Srinivasan, Murty and Nakra ); little is being undertaken on ‘examining how different population subgroups fare … in different welfare state regimes’ (Babra , 1101). No research has directly examined impacts of maternity leave policy on mothers' employment.…”
mentioning
confidence: 99%